Assessing the Impacts of Climate Change A Literature Review - Jamet, Stéphanie (OECD Publishing, 2009)
Climate change is expected to have significant implications for the world economy and, more broadly, for many areas of human activity. The purpose of this review is twofold. First, it is to summarise current estimates of the impacts of climate change and to explain how these estimates are built in order to identify the main sources of uncertainty and approximation affecting them. Second, the paper discusses how this uncertainty should influence policymaker?s decisions. A main conclusion of the review is that there are large uncertainties, which are not fully reflected in existing estimates of global impacts of climate change in monetary units. Nonetheless, despite these uncertainties, policy action may be justified, provided that policies are cost-effective, even if the marginal cost of GHG emissions mitigation exceeds the marginal damage of one additional ton of carbon. This is because two features of the impacts of climate change tilt the balance in favour of action: their irreversibility, and the risk that they are extreme
Keywords: Economics